DESEMPENHO TÉRMICO DE MATERIAIS PARA COBERTURAS E RESPECTIVAS INFLUÊNCIAS NAS ILHAS DE CALOR - Wenzel, Thaíse; Gutierrez, Grace (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
A current problem in big cities has been the heat island. This phenomenon causes the nocturnal temperatures to be higher, due to the way urban centers are built. The urban materials have a different thermal capacity and density than rural areas, causing the heat to be stored and released when the atmosphere is cooler in the evening/night. Roofs play an important role in the heat islands, since they are exposed to large amount of radiation. Google Maps 2017 was used to define the most common roof tiles in Belo Horizonte, MG, and then these types of tiles were exposed to heating in a lab and in the sun and their surface temperatures measured with a camera FLIR T420. The white metallic tile showed better performance in terms of heat island mitigation, and the cement slab, the worse.